2017
DOI: 10.7224/1537-2073.2016-039
|View full text |Cite
|
Sign up to set email alerts
|

Preferences for Multiple Sclerosis Treatments

Abstract: Background: The growing number of treatments for relapsing multiple sclerosis (MS) provides opportunities to consider patient preferences in treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In some cases, patients most valued symptom control, in other cases, patients prioritized delaying disability, and in yet other cases, patients focused on safety and avoiding AEs. Overall, patients preferred oral administration to injections, particularly frequent injections (Garcia-Dominguez et al, 2016;Lebrun et al, 2018;Mansfield et al, 2016;Poulos et al, 2016). One independent study found patients with MS placed more importance on DMT monthly out-of-pocket costs and mode of administration than AEs or efficacy (Hincapie et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…In some cases, patients most valued symptom control, in other cases, patients prioritized delaying disability, and in yet other cases, patients focused on safety and avoiding AEs. Overall, patients preferred oral administration to injections, particularly frequent injections (Garcia-Dominguez et al, 2016;Lebrun et al, 2018;Mansfield et al, 2016;Poulos et al, 2016). One independent study found patients with MS placed more importance on DMT monthly out-of-pocket costs and mode of administration than AEs or efficacy (Hincapie et al, 2017).…”
Section: Tablementioning
confidence: 99%
“…The conditional relative importance for each attribute was retrieved using the model estimates. As commonly seen in the literature [84][85][86][87] , a weight of 10 was assigned to the most important attribute, calculating the others relative to the most important attribute. Maximum acceptable risk post-hoc calculations reflect the trade-offs between specific attributes and a reduction in the risk of dying from cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Originally developed for consumer marketing purposes, medical researchers have used this https://doi.org/10.1017/cts.2022.372 method to analyze patient preferences in numerous disease areas including AD, multiple sclerosis, and exercise research [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…One approach to investigate the patient perspective is through a choice-based conjoint (CBC) experiment, a survey method designed to measure the preferences of patients and the tradeoffs they would tolerate in a treatment [25]. Originally developed for consumer marketing purposes, medical researchers have used this method to analyze patient preferences in numerous disease areas including AD, multiple sclerosis, and exercise research [26][27][28].…”
Section: Introductionmentioning
confidence: 99%